1991
DOI: 10.1063/1.104763
|View full text |Cite
|
Sign up to set email alerts
|

Electron and hole impact ionization coefficients in GaAs/Al0.45Ga0.55As/Al0.3Ga0.7As coupled well systems

Abstract: We have measured electron and hole multiplication factors and impact ionization coefficients in 550 Å GaAs/500 Å Al0.3Ga0.7As quantum wells with an intermediate Al0.45Ga0.55As barrier (50 and 100 Å) inserted in the well region. It is seen that while the measured value of α(E) is insensitive to the position of the intermediate barrier in the well, the value of β(E) is very sensitive. The value of α/β varies from less than unity to 5, depending on the position of this barrier. These results suggest that hole con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…4-6. The claims by Chin et al [2], and by others [3]- [7] that heterojunctions could be used in avalanche regions to reduce excess noise by tailoring the ratio via the band-edge discontinuity, have not been borne out [8]- [17]. Indeed, increasing the aluminum fraction above and hence band-edge discontinuity actually increases excess noise, as shown in Figs.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…4-6. The claims by Chin et al [2], and by others [3]- [7] that heterojunctions could be used in avalanche regions to reduce excess noise by tailoring the ratio via the band-edge discontinuity, have not been borne out [8]- [17]. Indeed, increasing the aluminum fraction above and hence band-edge discontinuity actually increases excess noise, as shown in Figs.…”
Section: Resultsmentioning
confidence: 68%
“…Choice of the layer heterostructure could therefore influence the value of which controls the degree of noisy feedback processes [1]. Subsequent experiments by numerous authors variously supported [3]- [7] or disagreed [8]- [15] with these predictions. However, the most compelling evidence comes from Chia et al [16], [17], who compared multiplication in both homojunction and single heterojunction Al Ga As-GaAs p -i-n diodes and found that the multiplication in heterojunction diodes, and hence the ionization coefficients, were not enhanced over those of corresponding homojunction diodes.…”
Section: Introductionmentioning
confidence: 94%
“…The reduction in excess multiplication noise in the superlattice APD structure was experimentally demonstrated by Kagawa et al, 215 who also found that the electron ionization coefficient is enhanced Figure 10.32 Three Al^GaovAs/GaAs mulriple-quantum-well configurations having a thin Alo^GaojsAs barrier inside the GaAs well (on the left) and measured ionization coefficients (on the right): (a) type-A, (b) type-B, and (c) type-C devices. (From Bhattacharya et al 217 ) over the value in GaAs at an electric field of 2.5xl0 5 V/cm when the barrier material is of a direct-gap type (Al x Ga,. x As, x<0.45).…”
Section: Algaas/gaas Heterostructuresmentioning
confidence: 99%
“…More recently, Bhattacharya et al 217 have measured the impact-ionization coefficients in A^GaojAs (500 A)/GaAs (550 A) quantum wells with an intermediate Al 045 Gao 55 As barrier (50 and 100 A) inserted in the well region. Their studied sample structures and measured results are shown in Fig.…”
Section: Algaas/gaas Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation